Les souterrains médiévaux du Limousin Approche méthodologique - Gady, Serge (Documents d'archéologie française, 1989)
Souterrains have in the past been the object of both varied and fanciful interpretations. Considered at different times to be places of refuge or worship, they have been attribued to periods ranging from pre-history to the French Revolution. The present study, first written as a doctoral thesis, examines94 souterrains in the Limousin region and analyses their geographical and historical significance. Research has included excavation of the Bois-du-Mont souterrain at Bessines-sur-Gartempe in the Haute-Vienne department. The result of the study proves that these underground chambers are related to rural settlement during IXth to XIIIth centuries. Archaeology provides firm evidence for when these structures were tunnelled, occupied and abandoned. The disciplined methodological approach of this work is exemplary in a field where scientific analysis has so far been virtually non-existent.